1976
DOI: 10.1017/s0094837300004966
|View full text |Cite
|
Sign up to set email alerts
|

Behavioral implications of saber-toothed felid morphology

Abstract: The claw equipped forelimbs have been shown to be an important hunting weapon for modern felids. In light of its functional importance, the claw retractile mechanism for modern felids was compared with that of the saber-toothed felids. In this regard, the functional anatomy of claw retraction for saber-toothed felids was found to be the same as that of modern forms. Body proportions of modern felids were also compared with saber-toothed felids and the relationship of their morphology to habitat structure and h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
80
0
5

Year Published

1992
1992
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 90 publications
(105 citation statements)
references
References 20 publications
4
80
0
5
Order By: Relevance
“…As many paleontologists have long demonstrated, Smilodon forelimbs show many robust features of their shafts and articular surfaces (Fig 1), compared to other large cats of comparable size [1][2][3][4][5][6][7][8][9][10]. For example, the forelimb bones of S. fatalis are roughly the same length as those of the tiger, P. tigris, but the shafts of the humerus, ulna and radius are noticeably thicker in S. fatalis than in P. tigris, and they have broad articular surfaces with much heavier bony ridges and processes.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…As many paleontologists have long demonstrated, Smilodon forelimbs show many robust features of their shafts and articular surfaces (Fig 1), compared to other large cats of comparable size [1][2][3][4][5][6][7][8][9][10]. For example, the forelimb bones of S. fatalis are roughly the same length as those of the tiger, P. tigris, but the shafts of the humerus, ulna and radius are noticeably thicker in S. fatalis than in P. tigris, and they have broad articular surfaces with much heavier bony ridges and processes.…”
Section: Discussionmentioning
confidence: 99%
“…For decades, paleontologists have noted that saber-toothed cats, such as the North American Pleistocene Smilodon fatalis, are more robustly built (Fig 1) than most felids [1][2][3][4][5][6][7][8][9][10]. Most recent authors have concluded that saber-toothed predators probably killed their prey with quick slashing bites to the throat, using powerful forelimbs to hold the prey down during attack [2][3][4][5][6][7][8][9][10].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The cache of large Pleistocene mammals at Rancho La Brea ranges in age from 10,000 to 38,000 years and includes such extinct species as the giant ground sloths (3 spp), dire wolf, tapir, camel, peccary, Colombian mammoth, mastodon, American lion, and the California saber-toothed cat. Anatomical studies and reconstruction of the extinct fossils from the tar pits have provided extensive insight into the faunal ecology of what is now termed the "Rancholabrean Land Mammal Age" and refers to the interval from 10,000 to about 400,000 years before the present in North America (1)(2)(3)(4)(5)(6)(7).…”
mentioning
confidence: 99%
“…Its muscular build and powerful limbs suggest that this saber-toothed cat used cunning and ambush rather than speed to capture relatively large prey (7). The function of the spectacular upper canine teeth still remains an issue of debate.…”
mentioning
confidence: 99%